(3JUMjM GdJUMja hJMQjQ GdJMQjas
(3ChdgG (B:s
(3GdMeO ddg GdPi dGjZdWI GNJdGa GdeSGFd hHYO aEf GdJUMja hGdJMQja bdeG Sde efgeG cHjQ NUhUkG eG CUHM Gdfbd SHjd Ch GdJbdjO Odjdg s
(3BNQgG (B:s
(3jfJgi HHGH HMQa GdjGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(4418) s
Keywords: (3GddZIs